1995
DOI: 10.1136/bmj.310.6975.289
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of HIV infection in a Scottish prison

Abstract: Objectives-To investigate the possible spread of HIV infection and its route of transmission among prison inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(160 citation statements)
references
References 24 publications
7
152
0
1
Order By: Relevance
“…[43][44][45][46][47] Whatever the rate may be, the majority of these sexual activities are likely to be unsafe due to the dearth of condoms in prisons. Injection drug use also occurs in prison and is associated with increased HIV risk; [47][48][49][50][51] tattooing may be an additional risk factor. 52 Using HIV testing to investigate HIV transmission within U.S. jails or prisons, some studies have found no strong evidence of intraprison spread of HIV, [53][54] while Mutter and colleagues found that 3% of a sample of individuals continuously incarcerated since 1977 had seroconverted to HIV-positive status.…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45][46][47] Whatever the rate may be, the majority of these sexual activities are likely to be unsafe due to the dearth of condoms in prisons. Injection drug use also occurs in prison and is associated with increased HIV risk; [47][48][49][50][51] tattooing may be an additional risk factor. 52 Using HIV testing to investigate HIV transmission within U.S. jails or prisons, some studies have found no strong evidence of intraprison spread of HIV, [53][54] while Mutter and colleagues found that 3% of a sample of individuals continuously incarcerated since 1977 had seroconverted to HIV-positive status.…”
Section: Resultsmentioning
confidence: 99%
“…There is research evidence from some developed and developing countries indicating that incarcerated IDUs are at risk of HIV infection in the prison environment, especially those who use injected drugs [18][19][20][21][22][23] ; there have been several reports of HIV outbreaks among drug-injecting prisoners. 24,25 Investigating sexual behavior and related risks for HIV infection among prisoners in Iran is very challenging. Same-gender sex is still very taboo in Iran and could be heavily punished.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Boutbreaks^of HIV infection among inmates in Scottish and Australian prisons, relating to injection drug use, have been reported. 42,43 A strong study from Thailand that included 1,209 injection drug users recruited in the community showed a rate of HIV seroconversion overall of 5.8/100 person-years and a rate of 35.0/100 person-years for those with a history of injection with incarceration since the prior HIV negative visit, suggesting that HIV seroconversion in the correctional setting in Thailand is not trivial. 44 Although international data suggests that intraprison transmission of HIV infection is most likely due to injection drug use, the context of U.S. prisons might differ from that of other countries.…”
Section: Hiv and Intraprison Transmission Studiesmentioning
confidence: 99%